PECULIARITIES OF FORMATION AND ACCUMULATION CONDITIONS OF NATURAL RESOURCES AND SAFE YIELD OF GOGHT-GARNI FRESH GROUNDWATER FLOW (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
In the article the results of hydro-geological investigations of the Goght-Garni ground water flow carried out with the purpose of overestimation of natural resources and operational reserves of fresh ground waters are summarized. It is established, that underlava and recent topography do not coincide, accumulation of groundwater flow occurs on buried under lavas ancient channels of the rivers. On water balance method it is established, that investigated groundwater flow recharges from the neighbouring basins either from Lake Sevan or the Vedi River Basin.
Keywords: Goght-Garni groundwater; water balance method; Lake Sevan; Vedi River Basin